Acinetobacter calcoaceticus CSY-P13 Mitigates Stress of Ferulic and p-Hydroxybenzoic Acids in Cucumber by Affecting Antioxidant Enzyme Activity and Soil Bacterial Community - Wu, Fenghui; An, Yan-Qiu; An, Yanrong; Wang, Xiu-Juan; Cheng, Zeng-Yan; Zhang, Yue; Hou, Xinwei; Chen, Chang-Xia; Wang, Li; Bai, Ji-Gang (Frontiers in Microbiology, 2018)
Ferulic acid (FA) and p-hydroxybenzoic acid (PHBA) are main phenolic compounds accumulated in rhizosphere of continuously cropped cucumber, causing stress in plants. Microbial degradation of a mixture of FA and PHBA is not well understood in soil. We isolated a strain CSY-P13 of Acinetobacter calcoaceticus, inoculated it into soil to protect cucumber from FA and PHBA stress, and explored a mechanism underlying the protection. CSY-P13 effectively degraded a mixture of FA and PHBA in culture solution under conditions of 39.37°C, pH 6.97, and 21.59 g L-1 potassium dihydrogen phosphate, giving rise to 4-vinyl guaiacol, vanillin, vanillic acid, and protocatechuic acid. During FA and PHBA degradation, activities of superoxide dismutase (SOD), catalase, ascorbate peroxidase, and dehydroascorbate reductase in CSY-P13 were induced. Inoculated into cucumber-planted soil containing 220 μg g-1 mixture of FA and PHBA, CSY-P13 degraded FA and PHBA in soil, increased plant height, and decreased malonaldehyde, superoxide radical, and hydrogen peroxide levels in leaves. CSY-P13 also enhanced SOD, guaiacol peroxidase, catalase, glutathione peroxidase, ascorbate peroxidase, monodehydroascorbate reductase, dehydroascorbate reductase, and glutathione reductase activities, increased ascorbate and glutathione contents, and elevated transcript levels of copper/zinc SOD, manganese SOD, and catalase in leaves under FA and PHBA. Moreover, CSY-P13 increased phosphatase, catalase, urease, and sucrase activities, and changed bacterial richness, diversity, and community composition by high throughput sequencing in cucumber-planted soil supplemented with the mixture of FA and PHBA. So CSY-P13 degrades the mixture of FA and PHBA in soil and mitigates stress from the two phenolic compounds in cucumber by activating antioxidant enzymes, changing soil bacterial community, and inducing soil enzymes.